Rancang Bangun Sistem Informasi Penjualan Roti Menggunakan Web-Services ( Studi Kasus : Yulia Bakery) - Nursusanto, Edy; Sulistiowati, Sulistiowati; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
yulia bakery is a small business that specializes in food, especially bread. yulia bakery has two branches located in different cities. yulia bakery producing bread every day to meet the sales and reservations. yulia in the bakery business processes have constraints in terms of sales services. consumers have to wait for the cashier to make a bill of sale and record sales into notebook sales. As for the constraints in the reports received by the owner can not be accepted every day. to overcome these problems then made a bread sales information system using web-services that will help service the cashier to be faster and also the reception received by the owner to be faster. reports received faster will help the owner to make the right decisions for yulia bakery